Elevated circulating fasting glucagon-like peptide-1 in surgical patients with aortic valve disease and diabetes - Krizhanovskii, Camilla (Diabetol Metab Syndr, 2017)
BACKGROUND: Diabetes is a risk factor for peripheral, coronary, and cerebrovascular disease. In contrast, results also indicate that patients with diabetes have reduced prevalence of aortic aneurysms, although the mechanisms remain largely unknown. We hypothesize that altered endogenous secretion of the intestinal hormone glucagon-like peptide-1 (GLP-1)—previously shown to protect from aneurysm formation, and governing many of the mechanisms thought to be involved in aneurysm formation—may provide insights into the mechanisms underlying the inverse relationship of diabetes and aneurysm. METHODS: We undertook a case–control study to characterize circulating plasma GLP-1 levels in diabetic and non-diabetic surgical patients with aortic valve disease, and with or without ascending aortic dilation. The cohort included patients with a bicuspid aortic valve (BAV), a common congenital disorder associated with ascending aortic aneurysm, as well as patients with a tricuspid aortic valve (TAV). RESULTS: In our patient group, diabetes was characterized by a significant increase in fasting plasma GLP-1 levels. Further, we show that aortic dilation in these patients was associated with a significant increase in fasting plasma GLP-1, although a significant increase in the intact and bioactive peptide could not be detected in BAV patients with aortic dilation. CONCLUSION: A subgroup of diabetic patients with aortic valve pathology have increased fasting plasma GLP-1 levels, which may be of importance for the low prevalence of aortic dilation in this patient group. Further, in TAV patients, GLP-1 secretion and plasma levels of intact GLP-1 are upregulated in association with aortic dilation, possibly indicating a compensatory mechanism. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13098-017-0279-0) contains supplementary material, which is available to authorized users.